Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis POE (Predict Observe Explain) Pada Materi Laju Reaksi Di Kelas XI SMAN 1 Sungayang - Yesi Oktalia; kuntum khaira (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research is based on the lack of availibity of student worksheets that use learning models, so that impact on the lack of activeness and understanding of student’s concepts. The purpose of this research is to produce a student worksheet based on POE (Predict-Observe-Explain) on the reaction rate material that is valid and practical. This study uses research and development research metods with development model (define, design, develop, and disseminate). This research was only carried out until development stage. The define stage is carried out to get an overview of the conditions in the field. After getting the conditions in the field, the next step is to design a student worksheet based on POE (Predict-Observe-Explain) on the rate material. After the process of designing the POE based student worksheet has been completed, it this continued white the validity and practicality test that exist at the develop stage. The result of this study indicate that: 1) student worksheet based on POE (Predict-Observe-Explain) have met the valid with 93,14% validation results,2) student worksheets based on POE (Predict-Observe-Explain) has met the very practical criteria with 91,05% response questionnaire result. The results of this study indicate that the chemical worksheets developed can be used as learning resource for student.